FASILITAS WISATA DI DESTINASI WISATA NGARAI SIANOK KECAMATAN GUGUK PANJANG KOTA BUKITTINGGI SUMATERA BARAT - Nazhirul Rifqi Alnev; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This study aims to get to know the tourist facilities in the Sianok canyon tourist destination, Guguk Panjang sub-district, Bukittinggi city, West Sumatra. Main facilities, Supporting Facilities and supporting facilities. This study uses a qualitative method with a descriptive approach to describe and explain the situation that occurs by collecting data and information in the field. The key informants in this study were the Ngarai Sianok Pokdarwis Management, the Head of RT Ngarai Sianok and Visitors. In this study, the data collection techniques used were interviews, observation and documentation. Based on the results of the study it can be concluded that the condition of the facilities available at the Sianok Canyon Tourism Object is quite good, however there are several facilities that are not optimally maintained due to the lack of managed facilities and lack of maintenance related to cleanliness from the manager such as canteens, toilets, prayer rooms and information centers. Keywords : Facilities, Sianok Canyon Bukittinggi